An Updated Review of Goserelin as Ovarian Protection in Premenopausal Breast Cancer - Berliana, Dini; Yulistiani, Yulistiani (Riwayat: Educational Journal of History and Humanities, 2023)
Premenopausal breast cancer is a serious medical challenge, with treatment focusing on inhibiting estrogen production to stop the growth of cancer cells. Goserelin, a gonadotropin hormone (GnRH) agonist, has been used to protect the ovaries and reduce estrogen levels in premenopausal women undergoing breast cancer therapy. Previous studies have provided evidence of Goserelin's efficacy and safety, but understanding continues to evolve. Therefore, we conducted this study to provide a recent update on the role of Goserelin in ovarian protection in premenopausal breast cancer. This study is an updated review that summarizes the relevant scientific literature on the use of Goserelin in ovarian protection in premenopausal breast cancer. We examined clinical research, randomized trials, and observational studies published in several leading academic databases. The results of these studies were analyzed and organized in the context of ovarian protection and therapeutic effects on patients. A review of the literature indicates that Goserelin remains an effective option in reducing estrogen levels in premenopausal women with breast cancer. Recent studies show continuity in Goserelin's role in reducing the risk of ovarian failure and side effects associated with estrogen inhibition, such as premature menopause. Apart from that, giving Goserelin in the form of monthly and 3-monthly implants is equally effective in controlling estrogen levels.